Historians debate the rise of the West - Daly, Jonathan W., author.
1 online resource (190 pages)
Keywords: "Discusses major scholars' evaluations of how Western civilization fits into modern world history. An introduction for students of Western civilization and world history to the main interpretations of Europe's rise that have been proposed since the middle of the twentieth century"--